Nueva lectura del ara votiva procedente del mvnicipivm Nova Avgvstanorvm (Lara de los Infantes, Burgos) - Jiménez de Furundarena, Agustín; Hernández Guerra, Liborio (Gerión. Revista de Historia Antigua, 2006)
The appearance of a votive Roman ara in The Archeological and Paleontological Museum of Salas de los Infantes (Burgos) allows to study the piece and to identify it with the inscription CIL II, 2851 transmitted by written tradition and disappeared for a long time.